Peningkatan Literasi Keuangan Islam Global Di CLSU Filipina - Zulpahmi Zulpahmi; Ummu Salma Al Azizah; Meita Larasati; Tohirin Tohirin (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This community service is carried out to the community and students in the Philippines about understanding about Islamic finance. Service activities are carried out face-to-face with lecture and discussion methods. Where between lecturers of the Faculty of Economics and Business and service partners directly meet in the same place. This activity will take place from July 4, 2023 to July 7, 2023 at Luzon State University, Philippines. Participants in this activity amounted to 40 people from students and the general public. This service activity generates awareness in global development, a deeper understanding of Islamic finance, inter-sector collaboration, participatory community empowerment, and the potential for positive change.